Association between CLOCK gene polymorphisms with circadian rhythm, chrononutrition, dietary intake, and metabolic parameters in adolescents - Özata Uyar, Gizem; Yıldıran, Hilal; Teker-Düztaş, Demet; Dalgic, Buket; Karakaş, Nazmi Mutlu; Çamurdan, Mahmut Orhun; Ergin, Filiz Başak; Ezgü, Fatih Suheyl (Frontiers in Public Health, 2024)
IntroductionCircadian Locomotor Output Cycles Kaput (CLOCK) is one of the transcription factors from the positive end of the molecular clock and regulates biological rhythm in mammals. Studies have shown that genetic variations in the CLOCK genes are associated with chronotype, sleep patterns, obesity, dietary energy, and nutrient consumption. Although interest in the field of chrononutrition continues to increase, investigations into the temporal aspects of dietary habits in adolescents are notably limited. This study aims to investigate the relationship between CLOCK rs3749474, rs4580704, and rs1801260 polymorphisms and circadian rhythm, metabolic parameters along with chrononutrition in adolescents.Materials and methodsThis cross-sectional study included a total of 300 adolescents between the ages of 11 and 18. Anthropometric measurements, dietary intake, chrononutrition, circadian as well as biochemical and lifestyle data were collected. CLOCK rs3749474, rs4580704, and rs1801260 gene polymorphisms were analyzed.ResultsThe CLOCK rs3749474 minor T allele carriers showed a statistically significant increased risk of being overweight or obese (OR: 2.106, p = 0.003). The minor G allele carriers of the CLOCK rs4580704 indicated statistically increased dietary energy intake and eating jetlag (p < 0.05). The frequency of snacking after the last meal was positively correlated with body mass index (BMI) z-scores in minor allele carriers of the CLOCK rs3749474 (β = 0.134, p = 0.003) and rs4580704 (β = 0.142, p = 0.012) variants. The minor G allele carriers of CLOCK rs4580704 revealed a negative link between breakfast frequency along with BMI z-scores (β = −0.178, p = 0.009). Individuals with the rs1801260 minor G allele showed a positive link between BMI z score and meal frequency (β = 0.367, p = 0.049). In CLOCK gene variants, minor allele carriers in addition to non-carriers had similar biochemical parameters and distribution of dietary intake at meal (p> 0.05).ConclusionThese results suggest that the impact of some chrononutrition behaviors on BMI z-scores are partially modulated by the variability in the CLOCK gene variants. Chrononutrition may be important in the shift toward “personalized nutrition” based on gene-diet interactions. For this reason, new dietary approaches may be implemented, including the circadian distribution of macronutrients and chrononutrition behaviors according to genotype. However, studies with larger samples in different populations are needed.